ANALISIS KOMPONEN BIAYA DAN TARIF ANGKUTAN PENYEBERANGAN DENGAN SIMULASI MODEL DINAMIS PADA ANGKUTAN LINTASAN SIBOLGA–TELUK DALAM PT. ASDP INDONESIA FERRY (PERSERO) - Hendy Karles; Dana Santoso (Universitas Mercu Buana, 2013)
Abstract: This research was initiated by an government policy which since January2011 at the Sibolga- Teluk Dalam route a subsidy budget are not given, as well as thequay demage of Teluk Dalam Port, so that there is no transportation ship at that route.At the urging of Nias Selatan government, finally PT. ASDP Indonesia Ferry (Persero)operating KMP. Raja Enggano without a subsidy budget and using pioneer tariff. In themain cost component in accordance with the rules prevailing in the government, then itcan be studied more in depth the current condition of pioneers tariff as proposed tariffadjustments to the government using dynamic simulation models. Development of adynamic model simulations conducted through the stages of identifying basicoperational costs, identify variables, simulation calculations, the validation results ofthe simulation calculations, scenario development and determination of policyalternatives. Results of dynamic simulation models using scenarios that have beendeveloped show that the average basic tariff satuan unit produksi (SUP) in the currentcondition is smaller than the average basic tariff SUP break-even point. It is influencedby considerations of operating ratio and working ratio is currently quite high so it isneeded the company's efforts to increase average basic tariff SUP in order to minimizelosses.Keywords: basic costs transport, transportation tariff, ferry crossing transportation,dynamic simulation model.